A comprehensive study of the magnetic properties of the pyroxenes series CaMgSi2O6–Co2Si2O6 as a function of Co content. (19th June 2018) - Delmonte, Davide; Gori, Claudia; Lambruschi, Erica; Mantovani, Luciana; Mezzadri, Francesco; Bersani, Danilo; Lottici, Pier Paolo; Gilioli, Edmondo; Solzi, Massimo; Tribaudino, Mario
Abstract: We report a detailed study on the magnetic properties of the pyroxene series M 2 M 1Si2 O6, with M 2  =  Ca and M 1  =  Mg, where magnesium and then calcium are progressively substituted by cobalt. For cobalt site occupancy larger than 0.7 at the M 1 site, a collinear antiferromagnetic phase is detected for T   <   T N1   =  12 K with a monodimensional character (i.e. M 1 site intra-chain order parallel to c axis). Moreover the magnetization easy axis has been estimated to lie roughly along the [1 0 1] direction. Cobalt content  ⩾0.5 at the M 2 site (overall content 1.5) determines the formation of a new independent antiferromagnetic order with higher Néel temperature, involving only the M 2 site intra-chain interactions. The incoming M 2 site order is accompanied by a lowering of the space symmetry which yields to a weakly ferromagnetic resultant due to spin canted distribution of the magnetic moments either along the M 1 or M 2 chains. Furthermore, metamagnetic transitions are observed for both M 1 and M 2 site intra-chain orders at relatively low critical magnetic fields, around 2 T, suggesting that this series of pyroxenes can be used as a model system for investigating the fundamental aspects of magnetism in the matter.